Kunstmacher 73. - Freivogel, Max (Schaffhausen : Museum zu Allerheiligen, 1973)
Barmettler, Agnes ; Bianchi, Cesare ; Binz, Jürg ; Bola, Tom ; Corradini, Bignia ; Corsin, Fontana ; Dickerhof, Urs ; Ducimetiere, Gerald ; Eisenegger, René ; Elsener, Ulrich ; Farny, Emilienne ; Fürer, Karl ; Gasser, Bruno ; Giger, H.R. ; Herzog, Josef ; Jäggli, Margrit ; Kaufmann, Markus ; Keller, Pierre ; Kocher, Lis ; Kohler-Chevalier, Walter ; Lüthi, Urs ; Melcher, Chasper Otto ; Muller-Brittnau, Willy ; Myrha, René ; Olesen, Muriel ; Ortelli, Jimmy ; Pfeiffer, Walter ; Poretti, Pierluigi ; Rappo, Marius ; Rouiller, Albert ; Rühlin, Reini ; Ryser, Peter ; Salvisberg, Benedikt ; Sandoz, Claude ; Schauenberg, Jean-Claude ; Scheurer, Jean ; Schibig, Philippe ; Schuhmacher, Hugo ; Schuldhess, Jörg ; Schwarz, Martin ; Schweizer, Benedikt ; Schweizer, Hans ; Signer, Roman ; Stooss, Urs ; Studer, Harold ; Tagwerker, Bernhard ; Tamagni, Giancarlo ; Togni, Giuliano ; Torres, Manuel ; Walz, Leo ; Wattenwyl, Peter Von ; Winnewisser, Rolf ; Wyss, Franz Anatol ; Zaugg, Rémy
biografie
Kunstmacher 73, Museum zu Allerheiligen, Schaffhausen, 18. August bis 7. Oktober 1973
Duits
kunstcatalogus